(untitled) (Global Journal of Medical Research, 2018)
Transmissible venereal tumor (TVT) is a sexually transmitted neoplasm that affects the external genitalia mainly although extragenital presentation has been reported. Its prevalence is variable, with developing countries presenting the highest rates due to large populations of stray dogs and poor breeding control. In the present study the prevalence of TVT was determined in the population that attends the Veterinary Hospital of the San Carlos of Guatemala University, being this the only university in the country that provides veterinary service to the public. We analyzed 1,125 medical records of patients who attended an outpatient clinic in 2016. The prevalence of TVT was 1.8%.